Spatio-Temporal Analysis of Carbon Monoxide (CO) Distribution According to Deforestation in West Kalimantan, Indonesia - Nurya Ramadhania; Murdawati; Devika Rahma Damayanti Yusuf; Widodo Eko Prasetyo (Departemen Teknik Geomatika ITS, 2026)
Carbon monoxide (CO) is a harmful air pollutant primarily produced through biomass burning, including forest fires and deforestation activities. West Kalimantan Province, which has undergone massive land cover change, is a crucial area for examining the link between deforestation and the increase in atmospheric CO concentrations. This study aims to analyze the spatial and temporal relationship between CO distribution and deforestation throughout 2024. CO data were obtained from Sentinel-5P satellite imagery, while deforestation detection was carried out using the Normalized Burn Ratio (NBR) and the Normalized Difference Vegetation Index (NDVI), derived from Sentinel-2A imagery. The NBR index was used to detect areas affected by fire or land conversion, while the NDVI reflects vegetation health conditions. The analysis results show that regions with increased NBR and decreased NDVI tend to have high CO concentrations. The Pearson correlation between NBR and CO indicates a very strong positive relationship, while the correlation between NDVI and CO shows a weak to moderate negative relationship. However, the dominance of cloud cover in most Sentinel-2A imagery in West Kalimantan potentially affects the quality and representativeness of the resulting vegetation data. This study highlights that deforestation significantly contributes to the decline in air quality, demonstrating that satellite-based remote sensing is an effective tool for air pollution monitoring and supporting environmental mitigation policies.